(3CeGdj GdTQja GdeQJVjs - (3Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, CHh GdbGSe ; GdTQja GdeQJVj,J (B436 (3g` s
(3ChdgG (B:s
(3bGd GdTQja GdEeGe JChjd BjI bGd Gddg Ld ef bGFd(B: "(3hEPG CQOfG Cf ofgdc bQjI CeQfG oeJQajgG aaSbhG ajgG aMb YdjgG Gdbhd aOeQfGgG JOejQG(B" (3aj gPg GdBjI hLhg ef GdJChjd cd efgG jHWd GdTHgg GdOGNdg s
(3BNQgG (B:s
(3aCNPJ HGdHjJjf Cdaj OjfGQ heG cGfG jSGhjGf YfOj OQgejf(B: (3Je fUa GdcJGH, hjJdhg aj GdLRA GdKGfj eLdS BNQg JChjd bhdg JYGdi(B:" (3oNdb GdEfSGf ef YLd SoCQjce BjGJj adG JSJYLdhf(B" s
(3GdfSNI HgG MhGTs
(3GfXQ GdLRA GdChd HGdCQbGe (B617-620 (3COH HYfhGf ZQQ GdaQGFOs
(3HGdfSNI agQSJ HeMJhjGJgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B60 s
Keywords: (3GdCOHs